Documents of Doubt: The Photographic Conditions of Conceptual Art, Heather Diack (2020). (1st June 2020) - Watson, Thomas
Review of: Documents of Doubt: The Photographic Conditions of Conceptual Art, Heather Diack (2020)Minneapolis, MN: University of Minnesota Press, 296 pp., ISBN 978-1-51790-757-0, p/bk, $30.00